Overexpression of Soybean Isoflavone Reductase (GmIFR) Enhances Resistance to Phytophthora sojae in Soybean - Cheng, Qun; Li, Ninghui; Dong, Lidong; Zhang, Dayong; Fan, Sujie; Jiang, Liangyu; Wang, Xin; Xu, Pengfei; Zhang, Shuzhen (Frontiers in Plant Science, 2015)
Isoflavone reductase (IFR) is an enzyme involved in the biosynthetic pathway of isoflavonoid phytoalexin in plants. IFRs are unique to the plant kingdom and are considered to have crucial roles in plant response to various biotic and abiotic environmental stresses. Here, we report the characterization of a novel member of the soybean isoflavone reductase gene family GmIFR. The cDNA of GmIFR was 1199 bp containing a 939 bp open reading frame encoding a polypeptide of 312 amino acids. Sequence analysis suggested that GmIFR contained a NAD(P) domain of 107 amino acids. Overexpression of GmIFR transgenic soybean exhibited enhanced resistance to Phytophthora sojae. Following stress treatments, GmIFR was significantly induced by P. sojae, ethephon (ET), abscisic acid (ABA), salicylic acid (SA). It is located in the cytoplasmic when transiently expressed in Arabidopsis protoplasts. The daidzein levels reduced greatly for the seeds of transgenic plants, while levels of genistein and glycitein had little change compared to that of control plants. Furthermore, we also found that the reactive oxygen species (ROS) content of transgenic soybean plants was significantly lower than that of control plants, suggesting an important role of GmIFR might function as an antioxidant to reduce ROS in soybean.